INGKAR SUNNAH DALAM SOROTAN IMAM SYAFI’I - Junaid Bin Junaid (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2018)
Sunnah is the second source of Islamic teachings after the Qur'an. Because the sunnah provides an explanation of the generality of one verse of the Qur'an which has a global meaning, so the meaning is clear. In this case, as one parcel of the generality. It's just that, the sunnah as a source of Islamic law there are still understandings or groups who reject it as one of the foundations or sources of Islamic law. And one of the ideas that reject the sunnah as a source of Islamic teachings or law is to understand the renegade of the sunnah. Where this understanding states that the Qur'an is the main and only source. All issues relating to the hablun min Allah and hablun min annas are all clearly illustrated in the Qur'an, so that the sunnah cannot be used as a source or basis. And according to the Shafi'ite Imama that it turns out that there is still a renegade understanding that there are moderate thoughts that can accept the sunnah as a foundation in Islamic law. That is still using the sunnah but the sunnah is valuable mut mutha who have many narrators and it is impossible to do lies in an action or deed. Keywords: Sunnah, Ingkar Sunnah, Imam Syafi’i